A review of modern advancements in micro drilling techniques. (October 2017) - Hasan, Mahadi; Zhao, Jingwei; Jiang, Zhengyi
Abstract: The demand for micro drilling with a diameter in a range of a few microns to several hundred microns is increasing in industries such as electronics, aerospace, medicine and automobiles, due to a significant uptake in the use of miniaturised products and devices. In order to satisfy the demand, a number of different micro drilling techniques have been developed. There has been, however, no report which explains, compares and contrasts all of these micro drilling techniques. This study examines the lasts micro drilling methods and techniques, categorises them into different groups, highlights recent developments and new trends, and depicts the future requirements in the field of micro drilling. Both conventional and non-conventional micro drilling techniques used in modern age applications are categorized. Conventional micro drilling makes use of drill bits of different configurations such as twist, spade, D-shaped, single flute, compound drill and coated micro drill, while non-conventional micro drilling involves electrical, chemical, mechanical and thermal means which include laser, EDM, ECM, SACE, electron beam, ultrasonic vibration or combinations of these approaches. We present here, a comparative study of conventional and non-conventional micro drilling techniques in order to show the potential and versatility of various micro drilling methods.